1990
DOI: 10.1177/016502549001300206
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Processes and Stages in the Acquisition of Cardinality

Abstract: This is a study of the level of children'·s understanding of cardinality, focusing on the difference between a true cardinality response and the .application of a mechanically learned rule. The authors also evaluate and discuss the possible relationship between cardinality and counting., The 'subjects were two groups of 32 preschool children, ranging in age from 4 years 3 moriths to 6 years 3 months. Experimental methodology included two large sets of tests (elements-cardinal vs cardinal-elements), using both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 18 publications
4
23
0
Order By: Relevance
“…By that time, his counting also was completely accurate-having been so for 2 months. This indicates that Spencer did not attribute special status to the last word in a count, as others have observed in previous research (Bermejo & Lago, 1990;Frye, Braisby, Lowe, Maroudas, & Nicholls, 1989;Fuson, 1988;Wynn, 1990;Wynn, 1992). Instead, he used the same response (i.e., ''two") that he used for similar queries in informal conversation and in spontaneous labeling.…”
Section: Performance On Structured Taskssupporting
confidence: 56%
See 1 more Smart Citation
“…By that time, his counting also was completely accurate-having been so for 2 months. This indicates that Spencer did not attribute special status to the last word in a count, as others have observed in previous research (Bermejo & Lago, 1990;Frye, Braisby, Lowe, Maroudas, & Nicholls, 1989;Fuson, 1988;Wynn, 1990;Wynn, 1992). Instead, he used the same response (i.e., ''two") that he used for similar queries in informal conversation and in spontaneous labeling.…”
Section: Performance On Structured Taskssupporting
confidence: 56%
“…They can match equivalent sets, label small numerosities, and use counting to determine cardinality (e.g., Bermejo, 1996;Bermejo & Lago, 1990;Fuson, 1988;Gelman & Gallistel, 1978;Huttenlocher, Jordan, & Levine, 1994;LeCorre & Carey, 2007;Mix, 1999;Mix, Sandhofer, & Baroody, 2005;Wynn, 1990). There have been different ideas about the origins of these skills-ideas that have generated abundant research on infancy and early childhood while largely ignoring toddlerhood (see Mix, Huttenlocher, & Levine, 2002, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when children use the ''counting on'' strategy, for instance, in solving an addition problem, one does not conclude that addition is a component of counting, because counting is only a means to achieve a goal (addition). We argue that the relationship between counting and cardinality is also similar to the relationship between means and goals, and between forms and functions (Bermejo & Lago, 1990;Saxe et al, 1987).…”
Section: Cardinality Principle Cardinality and Countingmentioning
confidence: 65%
“…Finally, in the Saxe, Guberman, and Gearhart (1987) model, counting and cardinality appeared as two different phenomena, just as forms and functions are different; and Bermejo (1996) and Bermejo and Lago (1990) found empirically that counting and cardinality are different, as means and goals are different. Furthermore, Bermejo and Lago found that children could count correctly-assign number-words and objects on a one-to-one correspondence-without giving a correct response in cardinality, and vice versa-offering a correct response in cardinality without counting correctly.…”
Section: Cardinality Principle Cardinality and Countingmentioning
confidence: 99%
See 1 more Smart Citation